Dying as a child in Roman Africa: gestures, practices and rituals (Proconsular Africa, Numidia, Caesarian Mauritania; 1st-3rd century CE) - (:unkn) unknown (My University, 2011)
The aim of this study is to characterize the gestures, practices and rituals about the children’s death in the Roman provinces of Africa Proconsularis, Numidia and Mauretania cesarean in the first three centuries AD. The available documentation is divided between numerous publications of cemeteries, more or less well documented depending on the date of excavation, and unpublished literature of the necropolis of Pupput (Hammamet), which provides for the first time a corpus large enough to be statistically credible. Because of their differences, the data are presented in various catalogs but analyzed simultaneously when associated to the same funeral sequence. At first, it was decided to study how corpses were managed from the localization of burial to its closure, then in a second time, the rituals performed in and around the grave. The initial postulate is that different burial practices adopted by families in charge of the funeral of their children depended on a number of factors. Among them, the children's age that determined the status of the deceased has been identified. According to archaeological and anthropological data studied, the ages of 6 months, 3 years and 7 years marked important steps in the socialization of the child in his family and the African society.
Keywords: African Research